2019
DOI: 10.1101/593996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The origins of anterograde interference in visuomotor adaptation

Abstract: 2Anterograde interference refers to the negative impact of prior learning on the propensity 3 for future learning. Previous work has shown that subsequent adaptation to two 4 perturbations of opposing sign, A and B, impairs performance in B. Here, we aimed to 5 unveil the mechanism at the basis of anterograde interference by tracking its impact as a 6 function of time through a 24h period. We found that the memory of A biased performance 7 in B for all time intervals. Conversely, learning from error was hinder… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…While many studies have shown that one's rate of learning 58,59 can be altered in numerous contexts such as savings 7,29,31,32,34,48,49 , meta-learning 31,48 , and anterograde interference 60 , we know comparatively little about how the brain controls the total amount of adaptation achieved with prolonged exposures to a perturbation. State-space models of learning 27,61 predict that asymptotic levels of performance are set by the balancing of learning and forgetting 17,62 .…”
Section: The Extent Of Adaptation Is Altered By a Decaying Memory Of ...mentioning
confidence: 99%
“…While many studies have shown that one's rate of learning 58,59 can be altered in numerous contexts such as savings 7,29,31,32,34,48,49 , meta-learning 31,48 , and anterograde interference 60 , we know comparatively little about how the brain controls the total amount of adaptation achieved with prolonged exposures to a perturbation. State-space models of learning 27,61 predict that asymptotic levels of performance are set by the balancing of learning and forgetting 17,62 .…”
Section: The Extent Of Adaptation Is Altered By a Decaying Memory Of ...mentioning
confidence: 99%
“…Earlier studies that documented modulation of error sensitivity focused on understanding the rate of 355 motor adaptation 16,42 in the context of savings 7,13,26,27,[43][44][45] , meta-learning 26,45 , and anterograde 356 interference 46 . Here we describe yet another feature of adaptation that appears to be controlled 357 through error sensitivity: the total extent of motor adaptation.…”
mentioning
confidence: 99%
“…While the session order (3° or 30°) was fully counterbalanced across participants, one potential concern in a withinparticipant design of learning is that there may be an effect of transfer or interference between sessions (Avraham et al, 2021;Krakauer et al, 2005;Lerner et al, 2020). For instance, experiencing a 30° clamped feedback in the first session may interfere with learning in the second session, resulting in attenuated learning.…”
Section: Experiments 1: the Impact Of Low Vision On Implicit Motor Adaptation For Small And Large Errorsmentioning
confidence: 99%
“…We thus analyzed the data of 52 unique participants with low vision: 12 participants completed only Experiment 1 (two sessions), 32 participants completed only Experiment 2 (one session), and 8 participants completed both experiments (three sessions). Sessions were spaced at least 24 hours apart to minimize any savings or interference (Avraham et al, 2021;Krakauer et al, 2005;Lerner et al, 2020).…”
Section: Participantsmentioning
confidence: 99%